Design of a Performance Measurement Framework for the Sudanese Construction Contractor’s Organizations - Sulieman, Hassan A.; Mohamed, Shamboul A. (University of Khartoum Engineering Journal, 2022)
This paper investigates the relations between the Sudanese construction contractor’s and other related institutions “resources” in term of project management capabilities, strategic decisions, strength of relationships with other parties and external factors, construction project performance and contractor’s organization performance from a resource based perspective. A structural equation (SEM) model was set to measure the seven latent variables through their constituent variables. Based on the findings of this study, it can be concluded that, the paper introduced a new method to measure performance in both qualitative and the quantitative terms.